The epidemic trend of rhinovirus in children from 2013 to 2023: a large sample study in China - Ting Shi; Yiwen Ni; Weiming Li; Linlin Huang (Italian Journal of Pediatrics)
Abstract Background This study described the prevalence trend of human rhinovirus(HRV) in children with acute respiratory infections(ARIs), which can warn people to interfere in advance and prevent the spread of rhinovirus. Methods We retrospectively collected the data on sex, age, admission time, discharge diagnosis and HRV reverse transcription polymerase chain reaction (RT-PCR) assay result of inpatients at Children’s Hospital of Soochow University from 2010 to 2023. Results There are 77,062 patients were enrolled, including 44,564 males (57.8%) and 32,498 females (42.2%). The positive rate of HRV during pre-, during- and post abolition-NPIs periods was 13.1%(5473/41875), 18.5%(3843/20800) and 21.0%(3031/14398), respectively. It was significant that the positive rate of HRV was gradually increasing with time(P<0.05). By multivariate regression analysis HRV prevalence were more common in male than female over all periods(P<0.05). HRV were more common in ≤ 1 year group than other age groups in pre-NPIs period (P<0.05). In during-NPIs and post-NPIs periods, HRV was more likely to occur in the 3-≤6 years groups. The seasonal trend of HRV showed a double peak each year, but the peak of it was advanced by one month in post-NPIs period. Conclusions Although the NPIs could not effectively prevent the spread of HRV, it changed the age and seasonal epidemic pattern of HRV in children.